2018
DOI: 10.18553/jmcp.2018.24.5.423
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Clinical Pharmacist-Led Comprehensive Medication Management on Chronic Disease State Goal Attainment in a Patient-Centered Medical Home

Abstract: Support for this study was provided to Wilson by the National Center for Advancing Translational Sciences, National Institutes of Health, through grant number ULI TR001860. The content of this article is solely the responsibility of the authors and does not necessarily represent the views of the National Institutes of Health. The authors have nothing additional to disclose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 14 publications
4
49
0
Order By: Relevance
“…The data analyzed in this study demonstrates that clinical pharmacists can have positive impacts on patients with diabetes in the primary care setting of a rural healthcare clinic. The improvement in the outcomes of goal attainment rates and decreases in hemoglobin A1c and blood pressure are consistent with findings in other studies [ 2 , 3 , 4 , 5 , 6 ]. The improvement in the primary outcome was statistically and clinically significant.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The data analyzed in this study demonstrates that clinical pharmacists can have positive impacts on patients with diabetes in the primary care setting of a rural healthcare clinic. The improvement in the outcomes of goal attainment rates and decreases in hemoglobin A1c and blood pressure are consistent with findings in other studies [ 2 , 3 , 4 , 5 , 6 ]. The improvement in the primary outcome was statistically and clinically significant.…”
Section: Discussionsupporting
confidence: 91%
“…Without the control group, it can still be inferred that the clinical pharmacy service has had positive impacts on patient outcomes as evidenced by the pre- and post-improvements in chronic disease state outcomes. Other studies have included the use of a control group and have reported improved outcomes in the group that includes a pharmacist [ 6 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Although this current study does not include a control group, the improvements in goal attainment and decreases in hemoglobin A1c and blood pressure are consistent with the findings from the other studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The United States incurs more than $500 billion in avoidable costs every year due to medication‐related morbidity and mortality . An approach to improve patient outcomes and mitigate the avoidable costs caused by suboptimal medication use is comprehensive medication management (CMM) . CMM is a patient‐centered practice that:
Ensures each patient's medications (whether they are prescription, nonprescription, alternative, traditional, vitamins, or nutritional supplements) are individually assessed to determine that each medication is appropriate for the patient, effective for the medical condition, safe given the comorbidities and other medications being taken, and able to be taken by the patient as intended
…”
Section: Introductionmentioning
confidence: 99%
“…1 An approach to improve patient outcomes and mitigate the avoidable costs caused by suboptimal medication use is comprehensive medication management (CMM). [2][3][4][5] CMM is a patient-centered practice that:…”
Section: Introductionmentioning
confidence: 99%